Probing composition distributions in nanoalloy catalysts with correlative electron microscopy. Issue 31 (10th March 2020) - Liu, Shikai; Gow, Isla; Davies, Thomas; Barnes, Alexandra; Sankar, Meenakshisundaram; Gong, Xiaoxiao; Howe, Alexander G. R.; Dixon, Michael; Hutchings, Graham J.; Kiely, Christopher J.; He, Qian
Abstract : A correlative electron microscopy method is introduced to statistically composition distributions among particles in nanoalloy materials, a parameter that is largely overlooked before. Abstract : Alloyed nanoparticles are important functional materials and have wide applications especially in heterogeneous catalysis and electrocatalysis. Controlled synthesis of nanoalloys is desirable in order to understand their structure–property relationships and further optimize their performance. While many synthesis methods have been developed, information on the resultant composition distributions among particles is often not available, and uniformity of composition from particle-to-particle is often incorrectly assumed. Such an analysis would require extensive work on a high-resolution analytical electron microscope, which has some drawbacks and the high-resolution equipment is not always readily accessible. We hereby introduce an alternative way for composition analysis of nanoalloys via a correlative electron microscopy approach, separating the size measurement (imaging) and composition analysis between TEM and SEM instruments. Using a case study of two AuPd nanoalloys which have very similar size distributions but significantly different composition distributions and catalytic activities, we demonstrate both the necessity of performing composition distribution analysis on ultrasmall nanoalloys and the feasibility of this method. We show that a more efficient X-ray analysis on nanoalloys can be done in an SEM due to intrinsically higher ionization cross-sections from the relatively lower energy ( e.g. 20 keV) electron beam and the possibility of using large probe currents and X-ray detectors with large collection angles.